The Challenges of Madrasah Management in Achieving Sustainability and Advantages in the Technological Digital Era - Buhari Luneto (Jurnal Madania, 2023)
This paper aims to discuss the problems faced in managing madrasas, particularly  in achieving high competitiveness in the current era of digital technology. This study uses exploratory descriptive data according to the theme and research objectives. The research data were analyzed through  in-depth evaluation and interpretation of the data, so that relevant important points were found related to the discussion of challenges and competitiveness faced by school management in modern times. This study found that the governance of Islamic schools faces various challenges, due to the fact that technology and the digital era are globalization trends that have positive and negative impacts. Madrasas as places where the pillars of Islam are in achieving educational goals based on Islam are expected to be able to take advantage of all these technologies by well, namely by balancing and aligning globalization trends, so as to give birth to creativity and active learning for students in facing competitiveness in today's global world.